Tree Species Diversity at Kebon Rojo, Blitar City - Marinda Sari Sofiyana (Bioma : Jurnal Ilmiah Biologi, 2023)
Tree Species Diversity at Kebon Rojo, Blitar City. Kebon Rojo is one of the open green spaces in Blitar City. This area has a variety of vegetation, one of which is trees. Diversity of tree species in this area has not been recorded. This study aims to determine the diversity of tree species at Kebon Rojo. The method used is the Je method by recording and documenting the diversity of trees in this area. The level of diversity was calculated using the Shannon Wiener index. The results of this study revealed that there were 322 trees belonging to 26 families, 36 species. The Shannon Wiener Diversity Index is 3.5. This value indicates the diversity of tree species at Kebon Rojo is high